Ca(2+) cycling in cardiomyocytes from a high-performance reptile, the varanid lizard (Varanus exanthematicus) - Galli, Gina L. J. (American Physiological Society, 2009)
The varanid lizard possesses one of the largest aerobic capacities among reptiles with maximum rates of oxygen consumption that are twice that of other lizards of comparable sizes at the same temperature. To support this aerobic capacity, the varanid heart possesses morphological adaptations that allow the generation of high heart rates and blood pressures. Specializations in excitation-contraction coupling may also contribute to the varanids superior cardiovascular performance. Therefore, we investigated the electrophysiological properties of the l-type Ca(2+) channel and the Na(+)/Ca(2+) exchanger (NCX) and the contribution of the sarcoplasmic reticulum to the intracellular Ca(2+) transient (Δ[Ca(2+)](i)) in varanid lizard ventricular myocytes. Additionally, we used confocal microscopy to visualize myocytes and make morphological measurements. Lizard ventricular myocytes were found to be spindle-shaped, lack T-tubules, and were ∼190 μm in length and 5–7 μm in width and depth. Cardiomyocytes had a small cell volume (∼2 pL), leading to a large surface area-to-volume ratio (18.5), typical of ectothermic vertebrates. The voltage sensitivity of the l-type Ca(2+) channel current (I(Ca)), steady-state activation and inactivation curves, and the time taken for recovery from inactivation were also similar to those measured in other reptiles and teleosts. However, transsarcolemmal Ca(2+) influx via reverse mode Na(+)/Ca(2+) exchange current was fourfold higher than most other ectotherms. Moreover, pharmacological inhibition of the sarcoplasmic reticulum led to a 40% reduction in the Δ[Ca(2+)](i) amplitude, and slowed the time course of decay. In aggregate, our results suggest varanids have an enhanced capacity to transport Ca(2+) through the Na(+)/Ca(2+) exchanger, and sarcoplasmic reticulum suggesting specializations in excitation-contraction coupling may provide a means to support high cardiovascular performance.